Estrutura produtiva, transporte e desigualdade : caracterização da acessibilidade ao trabalho na região metropolitana de Belo Horizonte - Paulo Henrique Góes Pinto (2020)
The characterization of accessibility conditions represents a possibility for urban policies to be formulated and subsidized. This analysis allows cities to be evaluated in terms of their main function, which is to enable access to opportunities. Furthermore, in addition to a normative perspective, the importance of accessibility for shaping cities is also recognized in the literature, and its analysis has permeated theories in the past two centuries in order to explain the patterns of urban development. Although many authors have dedicated themselves to the study of accessibility and how transport and land use policies impact it, there are still few studies dealing with this theme regarding cities in the global south, which is problematic in view of the particularities observed in their urbanization process. Given this context, this thesis proposes a methodological approach to characterize the accessibility in the metropolitan area of Belo Horizonte, considering walking and car driving as the commute modes and taking into account the location of jobs in different sectors as well as the sociodemographic spatial structure. The results obtained highlight the importance of understanding the peculiarities of the work accessibility patterns in order to formulate urban policies, since these patterns may vary depending on the economic sectors analysed and the modes of transport considered, impacting differently the various socioeconomic strata. Finally, it is worth noting that the analysis carried out allows us to characterize the productive structure in the Belo Horizonte metropolitan area in the light of transport costs, which represents a phenomenological contribution in line with the existing effort to promote integrated policies for transport and land use.